Towards a Global Community Educating for Tomorrow's World - Campbell, Jack; Baikaloff, Nick; Power, Colin (Education in the Asia-Pacific Region: Issues, Concerns and Prospects, 2006)
This book is the outcome of a global study undertaken on behalf of the World Education Fellowship (WEF) in collaboration with UNESCO. It begins with an analysis of the views of leading thinkers from 36 countries about the type of global community needed to ensure a peaceful and sustainable future, and the attributes that education programs need to develop in learners to develop their unique potentials and to be responsible members of a "diverse and restless global community." The second part the book focuses on the curriculum and pedagogical implications of the WEF study, including basic education, education for sustainable development, values education, conflict resolution and peace, and educating world citizens.